Life - Purves,William K.; Purves, William K.; Orians, Gordon H. ([S.l.] : Macmillan Education Australia, 1987)
CO-PUBLISHED BY SINAUER ASSOCIATES, INC., AND W. H. FREEMAN. More than any other general biology text, Life focuses students on the experiments that led to the discoveries that have shaped modern biology.
Keywords: biologi,life